Tindak Tutur Direktik Pidato Persuasif Siswa Kelas IX SMP melalui TikTok - Ismu Barokah Abror; Mukti Widayati; Nurnaningsih Nurnaningsih (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2023)
This study aims to describe the form of persuasive speech directive speech acts of grade IX MTsN 9 Gunungkidul students through TikTok. This type of research is descriptive qualitative. The data taken is speech that contains a form of directive speech act. The source of the data is persuasive speech videos of class IX students via TikTok. Data collection techniques use purposive sampling techniques. The instrument in this study is the researcher himself. The data collection method uses the listen method with free listening techniques, proficient involvement and record listening techniques. The technique of testing the validity of the data in this study by using source triangulation and method triangulation. Data analysis techniques use pragmatic analysis techniques. The results showed that of the 219 directive forms of speech found there were forms of asking (91), commanding (21), ordering (24), advising (71), and recommending (12). The directive speech act form asks to be marked with the words come, come, allow, please. The form of directive speech act reigns marked particle –lah, suffix –i, the word don't, must, oblige. The order directive speech act form is marked with the words hopefully, want, for, particle. The form of the act of advising uses the words should, should, so that, should, should, need, how good, and conjunctions cause and effect. The speech act form recommends using word several steps, in a way, doable, solutions to.